Exploring Pre-Service English Teachers’ Oral Communication Skill at Department of English Education of a University in Riau Province - Siregar, Siti Saidah (Innovative: Journal Of Social Science Research, 2025)
The aim of this research was to explore the level and challenges faced by pre service English teachers in improving their oral communication skill in English. This data was analyzed by using qualitative study. Data from the pre service English teachers were collected mainly using data documentation that helped by using the raters and group interview. The study shows that the pre service English teachers reported three main areas of challenges while using oral communication in micro teaching in front of the classroom; linguistic problems, non-linguistic problems, and Psychological Problems.